INTEGRATED MARKETING COMMUNICATIONS PT TELKOMSEL SUMBAGTENG REGION IN AN EFFORT TO INCREASE INDIHOME CONSUMERS - Masliati, Mardiyah; Zurani, Ikhma (Acta Diurna: Jurnal Ilmu Komunikasi, 2024)
The increasing public need for the internet has made companies compete in providing internet service provider products. One of the internet service provider products with many users in Indonesia is IndiHome, which is a product of PT Telkomsel. Despite being the largest internet service provider, it does not necessarily make IndiHome the only internet service that people are interested in, so it takes integrated marketing communication (IMC) or integrated marketing communication to retain consumers and offer products that are of interest to potential consumers. This is what is being done by PT Telkomsel Sumbagteng Region in the Pekanbaru City area in an effort to increase IndiHome consumers. This research uses the descriptive-qualitative method by collecting data through observation, interview, and documentation techniques. The results showed that the marketing communication carried out by PT Telkomsel Sumbagteng Region includes advertising through print media, electronic media, and digital media; sales promotion through event activities such as bazaars and giving prizes; public relations by establishing good relations with consumers and partnerships; personal selling through door-to-door and open car product offerings; and direct marketing through the use of media such as websites, WhatsApp, and telephone in offering products to consumers.